A infância no currículo de filmes de animação: poder, governo e subjetivação dos/as infantis - Maria Carolina da Silva (2008)
The objective of the present research is to analyze the subjectivities disposed by four animated movies, produced by Disney and Pixar: Toy Story (1995), Monsters INC (2001), Finding Nemo (2003) and The Incredibles (2004). Based on the Cultural Studies, especially in its post-structuralism approach, that works with Michel Foucault´s concepts, is consider that such movies teaches determined manners of how to be and proceed, considered adequate to their public, witch means that those movies have a cultural curriculum. The argument developed in this dissertation is that the curriculum of the investigated movies constructs childlike subjectivities through the presentation of two infancy models (the infancy-potential and the infancy-monster) and through the government of the childlike conducts. In this process, the movies dont only try to control the children, but teach how the adults must behave to be capable to lead the infancy. On the other hand, those movies dispose a heroic subjectivity that has as marks the courage, the friendship, the confidence and the partnership. To construct this subjectivity its necessary that the children articulate dominations techniques to the technologies of the self. Finally, its important to detach that the studied movies activate techniques related to the gender relations and, of that way, dispose gender subjectivities for its public. The study concludes that these different strategies utilized by the analyzed movies helps to built childlike subjectivities submitted to the adult figure. It also aims the necessity of others studies that help to understand how the infancy has being told in the contemporaneity in order to make possible the construction of new manners of how to be and proceed, so much for the childlike as for the adults that deal with them.